7th International Conference on Technologies & Business Models for Circular Economy: Book of Abstracts (University of Maribor Press, 2024)
The 7th International Conference on Technologies & Business Models for Circular Economy (TBMCE) was organized by the Faculty of Chemistry and Chemical Engineering, University of Maribor in collaboration with the Strategic Research and Innovation Partnership - Networks for the Transition into Circular Economy (SRIP- Circular Economy), managed by the Chamber of Commerce and Industry of Štajerska. The conference was held in Portorož, Slovenia, at the Grand Hotel Bernardin from September 4th to September 6th, 2024. EIT RawMaterials RIS Hub Adria, SPIRIT Slovenia Business Development Agency and Pomurje Technology Park (as part of the GREENE 4.0 and CI-Hub projects) have joined us as co-organizers. TBMCE 2024 was devoted to presentations of circular economy concepts, technologies and methodologies that contribute to the shift of business entities and society as a whole to a more responsible, circular management of resources. The conference program included panel discussions, plenary and keynote sessions, oral and poster presentations on the following topics: Sustainable Energy, Biomass and Alternative Raw Materials, Circular Business Models, Secondary Raw Materials and Functional Materials, ICT in Circular Economy, Processes and Technologies. Panel discussions addressed following topics: Circular Economy Transition in South East Europe, The transition to carbon neutrality in energy intensive industry, Valorization of used and contaminated wood, Circular economy trends in construction, Critical raw materials and circular economy transition, Industrial Symbiosis and its opportunities for industry, AI and circular economy. The event was under the patronage of Ministry of the Economy, Tourism and Sport and Ministry of Cohesion and Regional Development.